A Self‐Assembling Octahedral Aggregate of Poly(methyl methacrylate) Nanospheres on a Silver Substrate. Issue 2 (30th October 2015) - Chen, Shaoyun; Hu, Chenglong; Zhang, Weihong; Chen, Jian
Abstract: A large‐area, self‐assembling, octahedral aggregate composed of poly(methyl methacrylate) nanospheres (PMMA‐NS) was constructed by using a one‐step electrodeposition approach from an aqueous solution containing AgNO3 and PMMA‐NS as sacrificial electrolytes. The surface chain geometry of the product was revealed by Raman spectroscopy. The results revealed that the orientation of chains of the PMMA‐NS octahedron is different from that of the nonaggregated PMMA‐NS because of the interfacial interactions between the polymer chain and Ag metal. This can be explained by the crystal surface free energy of the octahedral Ag substrate, which gives rise to diverse conformations of the PMMA molecular chain at different surface regions of the silver substrate. In addition, the adsorptive properties of PMMA‐NS octahedra are such that the adsorbent–adsorbate system is cost‐effective, efficient and fast for the removal of dyes from contaminated wastewater. Abstract : Silver linings : A large‐area, self‐assembling, octahedral aggregate composed of poly(methyl methacrylate) nanospheres (PMMA‐NS) was constructed by a one‐step electrodeposition approach using an aqueous solution of AgNO3 and PMMA‐NS as sacrificial electrolytes. The surface chain geometry of the product was revealed by Raman spectroscopy, and its excellent adsorptive properties were studied (see figures).